1978
DOI: 10.1063/1.324414
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of annealed neon-, argon-, and krypton-ion implantation damage in silicon

Abstract: Comparative annealing studies were carried out upon Si layers implanted with Ne+, Ar+, and Kr+ ions. Ion doses were in the range 6×1014/cm2–6×1015/cm2, and ion energies were chosen so that the matrix damage had approximately the same depth for each ion type. Annealing was carried out in a N2/dilute O2 ambient or in vacuum at 600, 900, or 1100 °C. Implanted layer structures were studied using electron-microscope and ion-backscattering techniques. The orientation of the Si substrate and ion-beam heating effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…The beam flux was kept in the range of ͑3-6͒ ϫ 10 12 ions cm −2 s −1 , since it was shown that changes in the implantation flux can strongly affect the accumulation of defects. 35,42 Some implantations were carried out at room temperature while others were performed at temperatures ranging from 100 up to 600°C to avoid target amorphization. Anneals were performed in a vacuum of ϳ10 −7 torr at temperatures ranging from 400 to 1100°C for 30 min in a quartz tube within a tubular furnace.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The beam flux was kept in the range of ͑3-6͒ ϫ 10 12 ions cm −2 s −1 , since it was shown that changes in the implantation flux can strongly affect the accumulation of defects. 35,42 Some implantations were carried out at room temperature while others were performed at temperatures ranging from 100 up to 600°C to avoid target amorphization. Anneals were performed in a vacuum of ϳ10 −7 torr at temperatures ranging from 400 to 1100°C for 30 min in a quartz tube within a tubular furnace.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In Ar-implanted silicon it has been suggested that the large quantity of Ar present in a damaged Si layer is able to suppress the recrystallization of the layer. 35,53 In SiC, the presence of a high concentration of helium leads to the formation of different polytypes in the recrystallized area. 54…”
Section: A Amorphization-recrystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…3,7 Previous studies of inert gas ion implantation into Si and metals and annealing have shown that implanted ions tend to agglomerate or form bubbles depending on the implant dose. [12][13][14][15] In particular Xe has been shown to form bubbles in Si during annealing. 12 Although BF 2 implantation is capable of amorphizing the Si matrix, deeper preamorphizing implants ͑PAI͒, using higher mass ions such as Ge, are preferred since they suppress channelling effects and enable the spatial separation of the end-of-range ͑EOR͒ defects and the junction depth.…”
mentioning
confidence: 99%